2011
DOI: 10.4236/ijcm.2011.21005
|View full text |Cite
|
Sign up to set email alerts
|

Historical Cohort Study of the Efficacy and Safety of Piperacillin/Tazobactam Versus Fourth-Generation Cephalosporins for Empirical Treatment of Febrile Neutropenia in Patients with Hematological Malignancies

Abstract: We retrospectively evaluated the efficacy and safety of the combination drug piperacillin/tazobactam

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Previous studies mostly focused on the efficacy of fourth-generation cephalosporins; however, few clinical studies reported their associated renal function adverse effects (3)(4)(5). Cefpirome caused nephrotoxic symptoms in a rabbit model and the results suggested that cefpirome is potentially nephrotoxic compared to cefazolin, particularly in a single administration (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies mostly focused on the efficacy of fourth-generation cephalosporins; however, few clinical studies reported their associated renal function adverse effects (3)(4)(5). Cefpirome caused nephrotoxic symptoms in a rabbit model and the results suggested that cefpirome is potentially nephrotoxic compared to cefazolin, particularly in a single administration (6,7).…”
Section: Introductionmentioning
confidence: 99%